Study on the Influence of Closed-Cell Aluminum Foam on the Impact Performance of Concrete Pier after Equal Replacement with Stainless Steel Reinforcement - Xiwu Zhou; Honglong Zhang; Wenchao Zhang; Guoxue Zhang (Advances in Materials Science and Engineering)
In this study, the impact test of two groups of reinforced concrete piers protected by closed-cell aluminum foam is carried out by using the ultrahigh drop hammer impact test system. The purpose of this study is to explore the impact resistance and protective performance of closed-cell aluminum foam under the impact load on the concrete bridge pier after replacing the ordinary reinforcement with stainless steel reinforcement. The study results show that the impact force is related to the overall stiffness of the specimen, as well as to the failure mode. When the impact velocity is less than 1.42 m/s, the closed-cell aluminum foam is in an elastic or yielding stage. The change rate of impact force (231 and 97.5, respectively), tip displacement (33.5 and 18, respectively), and ultrasonic damage rate of the concrete in the two groups of specimen is relatively small, while the change rate of the two groups of specimen remains approximately consistent. In addition, when the impact is greater than 1.42 m/s and the closed-cell aluminum foam is in the densification stage, the change rate of the impact force (increase from 231 to 819 and from 97.5 to 984.5), the tip displacement (increase from 33.5 to 67 and from 18 to 62), and ultrasonic damage rate of concrete are larger, which results in an increase in the dynamic response of the structure.